A new biomarker for lung metastasis in non-seminomatous testicular cancer: De Ritis Ratio - Bozkurt, Muammer; Aghalarov, Samir; Atci, Muhammed Mustafa; Selvi, Oguzhan; Canat, Halil Lutfi (Aktuelle Urologie, 2022)
Purpose We aimed to show that the De Ritis Ratio (DRR) may be a new biomarker for lung metastasis in non-seminomatous Testicular Cancers (TC).Material and Methods Patients who underwent radical orchiectomy due to TC between January 2010 and January 2021 were included in the study. Demographic characteristics, preoperative laboratory and radiological findings and pathological data of the patients were recorded. The DRR was calculated from preoperative peripheral blood analysis.Results A total of 124 patients with non-seminomatous TC were included. Mean patient age was 30.67±7.45 years, and the mean tumour diameter was 4.69±2.55 cm. 61 patients had T1, 51 had T2, and 12 had T3 disease. 42 of them had lung metastasis; 82 of them had no lung metastasis. The optimal DRR threshold was 1.21 for lung metastasis. [Area Under the Curve (AUC): 0.724 with a sensitivity of 81% and specificity of 74%]. DRR was determined as an independent prognostic factor for lung metastasis in univariate and multivariate analyses (p=0.002).Conclusions A high preoperative DRR can be used to detect the presence of lung metastases in non-seminomatous TCs.
Keywords: Hodenkrebs; De Ritis Ratio; Lungenmetastasen; Aspartat-Aminotransferase; Alanin-Aminotransferase